2021
DOI: 10.3389/fcvm.2021.671655
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Gene-Based Diagnostic Signature for Ruptured Intracranial Aneurysms

Abstract: Background: Ruptured intracranial aneurysm (IA) is a disease with high mortality. Despite the great progress in treating ruptured IA, methods for risk assessment of ruptured IA remain limited.Methods: In this study, we aim to develop a robust diagnostic model for ruptured IA. Gene expression profiles in blood samples of 18 healthy persons and 43 ruptured IA patients were obtained from the Gene Expression Omnibus (GEO). Differential expression analysis was performed using limma Bioconductor package followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…ARG1, TPST1, S100A12, and PGLYRP1 were identi ed as key genes for aSAH (57,58). Of all down-regulated genes, CCR7 and CD27 were also identi ed as pivotal genes for aSAH (57,59). Therefore, we suggested that these 22 genes may be associated with immunity and in ammation and involved in the rupture of intracranial aneurysms and thus in the formation of SAH through potential mechanisms.…”
Section: Discussionmentioning
confidence: 87%
“…ARG1, TPST1, S100A12, and PGLYRP1 were identi ed as key genes for aSAH (57,58). Of all down-regulated genes, CCR7 and CD27 were also identi ed as pivotal genes for aSAH (57,59). Therefore, we suggested that these 22 genes may be associated with immunity and in ammation and involved in the rupture of intracranial aneurysms and thus in the formation of SAH through potential mechanisms.…”
Section: Discussionmentioning
confidence: 87%
“…Purple and blue represented positive and negative correlation between pathway and MLDGS, respectively. (44)(45)(46); however, they are all IA diagnostic models constructed using healthy subjects as controls and still without the in-depth assessment of molecular pathological features. In clinical settings, a biomarker with the ability to identify high-risk patients from the population with established IAs may be more appropriate for clinical decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…It is easier to design a new study and to obtain blood samples than aneurysmal specimens. In this category of studies, only three out of nine studies used data from at least two datasets [ 86 , 87 , 88 ], and six analyses were based on a single dataset [ 89 , 90 , 91 , 92 , 93 , 94 ]. Analytical methods used did not significantly differ when compared to tissue-based studies.…”
Section: Studies Based On Existing Datasetsmentioning
confidence: 99%
“…Analytical methods used did not significantly differ when compared to tissue-based studies. Two reports comprised validation cohorts [ 87 , 88 ]. Table 4 shows more details.…”
Section: Studies Based On Existing Datasetsmentioning
confidence: 99%